2013
DOI: 10.1007/s10534-013-9636-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of metallotionein isoforms complexes in hepatic cells of Mus musculus along cadmium exposure

Abstract: Characterization of Cd-binding proteins has great analytical interest due to the high toxicity of Cd to living organisms. Metallothioneins (MTs), as Cd(II)-binding proteins are of increasing interest, since they form very stable Cd chelates and are involved in many detoxification processes. In this work, inductively coupled plasma octopole reaction cell mass spectrometry and nanospray ionization time-of-flight mass spectrometry were used in parallel and combined with two-dimensional chromatography: size exclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…In terrestrial gastropods, the evolution of a MT isoform showing an extraordinary Cd 2+ -binding specificity was observed [ 89 ]. A recent study on mammalian MT1A revealed that the domain-specific order of the binding reaction and not the binding affinities account for the binding of zinc or Cd 2+ [ 90 ], whereas it had already been shown that MT1 is more significantly sequestering Cd 2+ than MT2 [ 91 ]. Several examples show that MT isoforms evolved to take over isoform-specific functions like Cd detoxification in mollusks [ 92 , 93 ], sea urchins [ 94 ], Drosophila [ 95 ], C. elegans [ 96 ], and Tetrahymena species [ 97 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terrestrial gastropods, the evolution of a MT isoform showing an extraordinary Cd 2+ -binding specificity was observed [ 89 ]. A recent study on mammalian MT1A revealed that the domain-specific order of the binding reaction and not the binding affinities account for the binding of zinc or Cd 2+ [ 90 ], whereas it had already been shown that MT1 is more significantly sequestering Cd 2+ than MT2 [ 91 ]. Several examples show that MT isoforms evolved to take over isoform-specific functions like Cd detoxification in mollusks [ 92 , 93 ], sea urchins [ 94 ], Drosophila [ 95 ], C. elegans [ 96 ], and Tetrahymena species [ 97 , 98 ].…”
Section: Resultsmentioning
confidence: 99%
“…3.3 Transcriptional profile in mouse following cadmium exposure Both Cd and ROS influence signal transduction processes via the modulation of transcription factors which lead to the transcriptional activation of different genes (Habeebu et al, 2000;Jara-Biedma et al, 2013 in the same range, demonstrating that the studied genes have a stable expression in these samples. From these results, we assumed that the study would not be exposed to misinterpretation by using sample pools.…”
Section: Measurement Of Lipid Peroxidation In Livermentioning
confidence: 99%
“…Compared to controls, the livers of Cd-exposed mice showed an impressive and time-dependent increase of Mt-1 mRNA molecules. We have previously reported that Cd exposure also induce MT expression at the protein level, by coupling HPLC with ICP-MS and ESI-MS which permitted us to identify Cd complexes with MT isoforms induced in Mus musculus (Jara-Biedma et al, 2013).…”
Section: Detoxification Of CD In Hepatic Cells Depends Mainly On the mentioning
confidence: 99%
“…In relation to this, the induction of Cd and Zn-metallothioneins in mice (Mus musculus) exposed to higher concentrations of Cd has been reported, 33 and these experimental data confirm the antagonistic interactions among Cd, Zn, Cu, as well as the differential rate of excretion of these elements from kidney/liver under increasing exposure. 34 It is well known that Cd exposure causes change in the distribution of endogenous Zn and Cu in tissues and biological fluids, since both metals play a protective role against Cd toxicity, due to their contribution in MTs induction (Fig.…”
Section: And Thementioning
confidence: 57%